Psychometric Properties of the Short Forms of the Social Interaction Anxiety Scale and the Social Phobia Scale in a Chinese College Sample - Ouyang, Xueyuan; Cai, Yan; Tu, Dongbo (Frontiers in Psychology, 2020)
This study was carried out to examine the factor structure and psychometric properties of the Social Interaction Anxiety Scale (SIAS) and Social Phobia Scale (SPS) in a sample of 1,001 Chinese college students (male: 34%; female: 66%). Confirmatory factor analysis (CFA) indicated that the two-factor shortened version of the SIAS-6/SPS-6 fit the data well. In addition, the item response theory (IRT) method confirmed the construct and items for the 12 items of the SIAS-6/SPS-6 with satisfactory discrimination, threshold parameters, and test information curve. It was concluded that the factor structure and psychometric properties of the SIAS-6/SPS-6 support their use for such assessment in a Chinese college sample.